2017
DOI: 10.1002/2017jg003779
|View full text |Cite
|
Sign up to set email alerts
|

Importance of coccolithophore‐associated organic biopolymers for fractionating particle‐reactive radionuclides (234Th, 233Pa, 210Pb, 210Po, and 7Be) in the ocean

Abstract: Laboratory incubation experiments using the coccolithophore Emiliania huxleyi were conducted in the presence of 234Th, 233Pa, 210Pb, 210Po, and 7Be to differentiate radionuclide uptake to the CaCO3 coccosphere from coccolithophore‐associated biopolymers. The coccosphere (biogenic calcite exterior and its associated biopolymers), extracellular (nonattached and attached exopolymeric substances), and intracellular (sodium‐dodecyl‐sulfate extractable and Fe‐Mn‐associated metabolites) fractions were obtained by seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Considering our incubation medium only included the bacteria, the incorporation of the particulate siderophore compounds could have become cumulatively more important in a more complex natural oceanic system that involves the interplay between bacteria, phytoplankton, zooplankton, and mineral particles. Phytoplankton are well-known to excrete a high abundance of expolymeric substances (EPS), enriched in proteins and polysaccharides, to the surrounding seawaters during their growth (Hassler et al, 2011;Quigg et al, 2016;Lin et al, 2017Lin et al, , 2020. Particle aggregation can occur by hydrostatic interaction of EPS containing a variety of negatively charged functional groups, resulting in hydrogen and metal ion bonding, as well as hydrophobic interactions that can lead to physicochemical cross linking (e.g., resulting in the protein/carbohydrate ratio being predictive for particle aggregation; Santschi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Considering our incubation medium only included the bacteria, the incorporation of the particulate siderophore compounds could have become cumulatively more important in a more complex natural oceanic system that involves the interplay between bacteria, phytoplankton, zooplankton, and mineral particles. Phytoplankton are well-known to excrete a high abundance of expolymeric substances (EPS), enriched in proteins and polysaccharides, to the surrounding seawaters during their growth (Hassler et al, 2011;Quigg et al, 2016;Lin et al, 2017Lin et al, , 2020. Particle aggregation can occur by hydrostatic interaction of EPS containing a variety of negatively charged functional groups, resulting in hydrogen and metal ion bonding, as well as hydrophobic interactions that can lead to physicochemical cross linking (e.g., resulting in the protein/carbohydrate ratio being predictive for particle aggregation; Santschi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these tracer applications are generally resting on inferences from correlations of isotopic ratios with bulk particle properties, experimental evidence reveals organic compound-specific scavenging and partitioning for different radionuclides, either in particulate or in colloidal phases (Hayes et al, 2015a,b;Lam et al, 2015;Lin et al, 2015). Furthermore, while previous focus was on inorganic matter as the main binding agents (e.g., opal, carbonate, and lithogenic; Chase et al, 2002;Guo et al, 2002;Roy-Barman et al, 2009;Lin et al, 2014), more recent experimental studies reveal the role of specific organic matter compounds in the scavenging of different radionuclides in marine environments (Roberts et al, 2009;Xu et al, 2011a;Chuang et al, 2014Chuang et al, , 2015aLin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the global oceans, diatom and coccolithophores serve as the most important contributors to global oceanic primary production and to carbon flux (Nelson et al, 1995;Armbrust, 2009), whereby in-situ production and excretion of biogenic materials account for the majority of natural organic matter in the water column. During phytoplankton growth, secretion of fresh biopolymers (Chin et al, 1998;Santschi et al, 1998;Quigg et al, 2016) was shown to provide the strongest binding agents for different radionuclides compared with the naked diatom frustule (Chuang et al, 2014) or coccosphere (Lin et al, 2017(Lin et al, , 2020. Furthermore, particle-reactive radionuclides can partition differently between diatom-and coccolithophore-predominated systems or among different biopolymer fractions of diatom or coccolithophore cells, which were attributed to different organic composition between different biopolymer fractions, and thus, to different affinities of the radionuclides to these fractions (Chuang et al, 2015b;Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations